2022
DOI: 10.1182/blood.2022016867
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of AML in adults: 2022 recommendations from an international expert panel on behalf of the ELN

Abstract: The 2010 and 2017 editions of the European LeukemiaNet (ELN) recommendations for diagnosis and management of acute myeloid leukemia (AML) in adults are widely recognized among physicians and investigators. There have been major advances in our understanding of AML, including new knowledge about the molecular pathogenesis of AML, leading to an update of the disease classification, technological progress in genomic diagnostics and assessment of measurable residual disease, and the successful development of new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
1,588
1
20

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,458 publications
(1,631 citation statements)
references
References 204 publications
22
1,588
1
20
Order By: Relevance
“…Several studies reported that patients with t(9;11) had better treatment outcome than patients with other rearrangements involving 11q23/KMT2A [11,13,[56][57][58][59], which placed patients with t(9;11) in the intermediate-risk category in both prognostic categorizations based solely on cytogenetic data [11,13] and in classifications combining cytogenetics with selected molecular genetic findings, like 2010 [60] and 2022 [20] ELN classifications. However, a more favorable prognosis of patients with t(9;11) was observed in studies analyzing exclusively [13,57] or mostly [11,56,58] adults younger than 60 years.…”
Section: Aml With Kmt2a Rearrangementmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies reported that patients with t(9;11) had better treatment outcome than patients with other rearrangements involving 11q23/KMT2A [11,13,[56][57][58][59], which placed patients with t(9;11) in the intermediate-risk category in both prognostic categorizations based solely on cytogenetic data [11,13] and in classifications combining cytogenetics with selected molecular genetic findings, like 2010 [60] and 2022 [20] ELN classifications. However, a more favorable prognosis of patients with t(9;11) was observed in studies analyzing exclusively [13,57] or mostly [11,56,58] adults younger than 60 years.…”
Section: Aml With Kmt2a Rearrangementmentioning
confidence: 99%
“…Recently, the Francophone Group of Hematological Cytogenetics suggested that to standardize cytogenetic practice, a complex karyotype with 3 chromosome abnormalities should be defined as a low, one with 4 aberrations as an intermediate and one with 5 or more abnormalities as a highly complex karyotype [71]. The most recent definition proposed by ELN denote complex karyotype as containing ≥3 abnormalities in the absence of "other class-defining recurring genetic abnormalities" and does not consider as complex karyotypes with three or more trisomies in the absence of structural abnormalities [20].…”
Section: Complex Karyotype and Its Clinical Significance In Amlmentioning
confidence: 99%
See 3 more Smart Citations